Lithium‐ion battery modelling for the energy management problem of microgrids. Issue 3 (1st February 2016) - Tenfen, Daniel; Finardi, Erlon C.; Delinchant, Benoit; Wurtz, Frédéric
Abstract : This study presents a mathematical model of lithium‐ion (Li‐ion) batteries in the energy management (EM) problem of a microgrid (MG). In this study, the authors develop a detailed model of Li‐ion batteries that considers the degradation cost associated with operation, controllable and uncontrollable charging ramps, other limits, and the operating characteristics provided by the manufactures. The Li‐ion battery degradation cost is analysed using different approaches and is compared with modelling without this cost, using a quadratic degradation cost, and using a piecewise degradation cost. Furthermore, this cost is analysed using a linear cost that takes the life expectancy based on the number of cycles of the battery into account. To analyse the proposed method and other modelling approaches, the authors examine the battery model in an EM problem in an MG. This MG, which can be connected to the main grid, also uses wind and photovoltaic as generation resources, in addition to a backup generator. The EM problem is modelled as a deterministic mixed‐integer linear (or quadratic) problem; the results of eleven different cases are used in the analysis of the proposed Li‐ion battery model for a 24 h planning horizon.